2011
DOI: 10.1007/s10207-011-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic retention: what does your mobile phone reveal about you?

Abstract: The global information rich society is increasingly dependent on mobile phone technology for daily activities. A substantial secondary market in mobile phones has developed as a result of a relatively short life-cycle and recent regulatory measures on electronics recycling. These developments are, however, a cause for concern regarding privacy, since it is unclear how much information is retained on a device when it is re-sold. The crucial question is: what, despite your best efforts, does your mobile phone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…As a result of their increased (and increasing) functionality, smartphones are able to access and store personally identifying information. Potentially private data such as medical details, sensitive business information, personal pictures and voicemails have been recovered from mobile devices, despite being deleted [2]. This confirms that users do indeed store these kinds of data on their devices.…”
Section: Introductionsupporting
confidence: 54%
“…As a result of their increased (and increasing) functionality, smartphones are able to access and store personally identifying information. Potentially private data such as medical details, sensitive business information, personal pictures and voicemails have been recovered from mobile devices, despite being deleted [2]. This confirms that users do indeed store these kinds of data on their devices.…”
Section: Introductionsupporting
confidence: 54%
“…From an evidentiary perspective, the smartphone can be considered a treasure trove of forensic evidence. A recent study recovered more than 11,000 data artifacts from just 49, predominately low-end, devices [25]. As with a traditional mobile phone, the smartphone not only stores call logs, text messages and personal contacts, but it also has the ability to store web-browsing artifacts, email messages, instant messenger lots, GPS coordinates, as well as third-party application related data [26][27][28].…”
Section: Related Workmentioning
confidence: 99%
“…Recent work from forensic scientists, privacy researchers and computer scientists has found that user generated metadata created with mobile devices and Internet connected mobile networks leave little room for anonymity or obfuscation (boyd & Crawford, 2012;Brunton & Nissenbaum, 2013;de Montjoye et. al, 2013;Glisson, et. al, 2011;Mayer & Mutchler, 2014;Willassen 2003;Willassen, 2005).…”
Section: Metadatamentioning
confidence: 98%